Вища геодезична освіта у Львові до 1880 року (хронологія передісторії виникнення кафедри геодезії Львівської політехніки) - Дрбал, О.; Тревого, І.; Лехнер, Ї.; Drbal, O.; Trevoho, I.; Lechner, J. (Видавництво Львівської політехніки, 2023)
У хронологічній послідовності наведено події виникнення і розвитку вищої геодезичної освіти у Львові, починаючи від виникнення кафедри математики у Львівській (Єзуїтській) академії у 1744 р., де розпочали викладати практичну геометрію, до виникнення кафедри геодезії і сферичної астрономії у Львівській політехніці в 1871 р. і відкриття при ній астрономічної обсерваторії у 1880 р. Висвітлено внесок у розвиток освіти і науки найяскравіших представників професорсько-викладацького складу різних національностей та наведено рисунки із виданих навчальних посібників.

The events of the emergence and development of higher geodetic education in Lviv are described in chronological order, starting from the establishment of the Department of Mathematics at the Lviv (Jesuit) Academy in 1744, where practical geometry was then taught, to the establishment of the Department of Geodesy and Spherical Astronomy at the Lviv Polytechnic in 1871 .and the opening of an astronomical observatory at it in 1880. The contribution to the development of education and science by the brightest representatives of the teaching staff of various nationalities is described, and the drawings of the textbooks prepared by them are given.
Higher geodesic education in Lviv until 1880 (chronology of the prehistory of the Department of Geodesy of the Lviv Polytechnic
Keywords: практична геометрія; градусні вимірювання; геодезія; топографічне знімання; кадастр нерухомості; астрономічна обсерваторія; історія астрономії; геодезії; картографії та кадастру; practical geometry; degree measurements; geodesy; topographic survey; real estate cadastre; astronomical observatory; history of astronomy; geodesy; cartography and cadastre in Western Ukraine; 528 (091); (477.83-21)